2014
DOI: 10.1002/mrc.4044
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative and qualitative 1H, 13C, and 15N NMR spectroscopic investigation of the urea–formaldehyde resin synthesis

Abstract: Urea-formaldehyde resins are bulk products of the chemical industry. Their synthesis involves a complex reaction network. The present work contributes to its elucidation by presenting results from detailed NMR spectroscopic studies with different methods. Besides (1)H NMR and (13)C NMR, (15)N NMR spectroscopy is also applied. (15)N-enriched urea was used for the investigations. A detailed NMR signal assignment and a model of the reaction network of the hydroxymethylation step of the synthesis are presented. Be… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 89 publications
1
45
0
Order By: Relevance
“…41 More recently, Lavric reported the accurate mass determination of melamine-formaldehyde resins by HPLC-MS with two ionization techniques, electrospray ionization (ESI) and atmospheric pressure chemical ionization (APCI) with a source temperature of 350 C. 42 In the present work, a high resolution LC/ESI-TOF-MS system was used to characterize our oligomers. The detection m/z window was in the scan range from 103 to 3000 with a source temperature at 325 C. This temperature was controlled to prevent possible reactions in the source and was in the same range than those reported with melamine resins.…”
Section: Resultsmentioning
confidence: 97%
“…41 More recently, Lavric reported the accurate mass determination of melamine-formaldehyde resins by HPLC-MS with two ionization techniques, electrospray ionization (ESI) and atmospheric pressure chemical ionization (APCI) with a source temperature of 350 C. 42 In the present work, a high resolution LC/ESI-TOF-MS system was used to characterize our oligomers. The detection m/z window was in the scan range from 103 to 3000 with a source temperature at 325 C. This temperature was controlled to prevent possible reactions in the source and was in the same range than those reported with melamine resins.…”
Section: Resultsmentioning
confidence: 97%
“…In contrast, urea reacts with up to three units of formaldehyde per molecule under similar conditions (Becher [8] and others [4,[9][10][11][12] ). Because of the fact that 1,3-dimethylurea reacts only with one molecule of formaldehyde, the formation of polymeric chains is not possible, but a single condensation takes place.…”
Section: Similarities Differences and Limitations Of The Model Systemmentioning
confidence: 90%
“…Chemical shifts of the species identified in the reaction system 1,3-dimethylurea-formaldehyde, Part I (hydroxymethylation products). The chemical shifts of formaldehyde FA and the methyleneglycols MG 1:::10 can be found elsewhere [4,14,15] [23,24] Because of this evidence, the formation of ether bridges has been taken into account in the present study in the reaction kinetic model. More details on the indications supporting the formation of ether bridges as found during the course of the present work are provided in the Supplementary Information.…”
Section: Ether Bridgesmentioning
confidence: 97%
“…The spectra were recorded at 150 MHz with 400-600 scans accumulated. The observed chemical shifts were assigned by referring to the assignments in the literature [3][4][5][6][7][8][9][10][11][12][13][14][15].…”
Section: Procedures For Quantitative 13 C-nmr Determinationmentioning
confidence: 99%
“…After the acidic condensation, the pH is adjusted back to alkaline and the additional urea (the second urea) is added to lower the F/U molar ratio to 0.9-1.2, aiming to capture the un-reacted formaldehyde. Although intensive studies have been completed to investigate the chemical structures of resin polymers by employing nuclear magnetic resonance d(NMR) analysis [3][4][5][6][7][8][9][10][11][12][13][14][15], our survey of the literature showed that the effects of post-added urea on the UF polymers were not focused or well-discussed. However, this issue is important for better understanding the relationship between low molar ratio and poor performance of the resin.…”
Section: Introductionmentioning
confidence: 99%